Penggunaan Media Pohon Hitung untuk Meningkatkan Kemampuan Kognitif Anak Kelompok A TKN Sukorejo - hariyatin hariyatin (Jurnal Pendidikan : Riset dan Konseptual, 2019)
ABSTRAK: This research background in cognitive abilities of children in low count using tree count, especially at the time of calling the numbers 10-20, the symbol pair numbers and called the addition and subtraction with objects This study aims to describe the steps the use of the media tree count and tree count describes the use of media in improving the cognitive abilities of children in the kindergarten group A Sukorejo Blitar City District. The research was conducted at TKN Sukorejo with the study design used was a class act design (TOD) model Kemiss and Mc Taggart. In each cycle consists of several stages, namely planning, implementation, observation, and reflection. In this study researchers collaborate with classroom teachers. The results showed that the use of the media tree count in the learning activities refer to numbers 1-20, numbers and symbols mentioned pair addition and subtraction with objects shown to develop children's cognitive abilities Ability TK.Pada I cycle the average child reaches 69.99% increase to 88.51% in cycle II. Marked increase with increasing cognitive abilities through the call numbers 1-20, numbers and symbols mentioned pair addition and subtraction with objects. Based on this research, called the numbers 1-20, numbers and symbols mentioned pair addition and subtraction by using media objects counting tree can enhance children's cognitive abilities in math. encouraged to try to study with another problem with using other media, namely in the field of physical motor development, habituation, art, and language.